2023
DOI: 10.2903/j.efsa.2023.7967
|View full text |Cite
|
Sign up to set email alerts
|

Flavouring Group Evaluation 217 Revision 3 (FGE.217Rev3): consideration of genotoxic potential for α,β‐unsaturated ketones and precursors from chemical subgroup 4.1 of FGE.19: lactones

Abstract: The Panel on Food Additives and Flavourings of the European Food Safety Authority was requested to evaluate the genotoxic potential of four flavouring substances [FL‐no: 10.023, 10.030, 10.057 and 13.012] from subgroup 4.1 of FGE.19. For three of these substances [FL‐no: 10.023, 10.030 and 13.012], the concern for genotoxicity has been ruled out in previous revisions of Flavouring Group Evaluation 217 (FGE.217). However, in FGE.217Rev2, a concern for genotoxicity could not be ruled out for 3a,4,5,7a‐tetrahydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
(11 reference statements)
0
0
0
Order By: Relevance
“… 82nd JECFA report (JECFA, 2016a ) and 82nd JECFA toxicology monograph (JECFA, 2017 ). Genotoxicity data evaluated in FGE.217Rev3 (EFSA FAF Panel, 2023 ). EFSA scientific opinion on FGE.80 (EFSA, 2008a ).…”
Section: Data and Methodologiesmentioning
confidence: 99%
See 4 more Smart Citations
“… 82nd JECFA report (JECFA, 2016a ) and 82nd JECFA toxicology monograph (JECFA, 2017 ). Genotoxicity data evaluated in FGE.217Rev3 (EFSA FAF Panel, 2023 ). EFSA scientific opinion on FGE.80 (EFSA, 2008a ).…”
Section: Data and Methodologiesmentioning
confidence: 99%
“…2223 in its 82nd meeting (JECFA, 2016a , 2016b , 2017 ). This substance was evaluated by EFSA in FGE.217Rev3 (EFSA FAF Panel, 2023 ), where it was concluded that the concern for genotoxicity for [FL‐no: 10.057] could be ruled out. Therefore, it can be evaluated through the procedure for which purpose it has now been added to this revision 2 of FGE.80.…”
Section: Data and Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations